HUBUNGAN PENGGUNAAN GADGET DENGAN TANDA DAN GEJALA KESEHATAN MENTAL ANAK SISWA SEKOLAH DASAR DI SD NEGERI PAMANUKAN SEBRANG I KABUPATEN SUBANG - Sutandi, Deby Noer; Simatupang, Lenny Lusia (Excellent Midwifery Journal, 2024)
Children's mental health is the mental condition of children who do not experience mental illness, and the ability to think clearly, control emotions, and socialize with children their age. Poor mental health during childhood can cause more serious behavioral disorders due to mental and emotional imbalance, as well as the child's poor social life. Objective: This research is to determine the relationship between gadget use and signs and symptoms of mental health of elementary school students at the Pramuka Public Elementary School, Pamanukan Sebrang I, Subang Regency. Method: Quantitative research method with a cross sectional survey, data collection was carried out using the Simple Random Sampling technique for a total of 93 students, the instrument used a questionnaire. The Chi-Square test was used to analyze research data. Results: The results of this study show that there is a relationship between the use of gadgets and signs and symptoms of mental health at the Pramuka I Public Elementary School, Subang Regency with a p value of 0.684 > 0.05. Conclusion: There is a significant relationship between the use of gadgets and the signs and symptoms of mental health of students at the Pramuka Public Elementary School, Sebrang I, Subang Regency. It is hoped that the school can help provide an understanding of the use of gadgets and the signs and symptoms of mental health of students as well as carry out prevention and treatment to ensure children's mental health. still maintained at the Pramuka Public Elementary School, Sebrang I, Subang Regency.